Effects of Water Stress on Maize Cultivars During the Vegetative Stage - Ashraf, M (Annals of Arid Zone, 2016)
The effects of water stress on the vegetative growth of nine cultivars of maize, Agaifi 72, Akbar, Comp 15, EV 1081, EV 5081, EV 6081, Sadaf, Sultan and Sunehri, grown for 7 weeks, were assessed. There were close relationships between biomass production and wa ter content, and water relations of a’l cultivars in response to repeated droughting except in cv Agaiti 72. The cv Akbar and EV 60S!, having lower fresh and dry biomass of ;hoot and water content, had both low leaf water potential (if; w) and turgor potential (tpp). By contrast, the high biomass producing cv Comp IS, EV 108, Sadaf, Sultan, and Sunehri had higher I/Iw and !fP. Selection criteria based on high leaf water potential and turgor potential during early vegetative growth are, therefore, suggested as means for screening maize cultivars/lines. Sufficient intercultivar variation in response to water stress was observed suggesting that selection of individuals with increased drought resistance seems possible within maize.